Synthesis and self-assembling properties of 4, 6−O-benzylidene acetal protected D-glucose and D-glucosamine β−1, 2, 3−triazole derivatives. (22nd May 2018) - Chen, Anji; Okafor, Ifeanyi S.; Garcia, Consuelo; Wang, Guijun
Abstract: Sugar based low molecular weight gelators (LMWGs) are useful small molecules that can form reversible supramolecular gels with many applications. Selective functionalization of common monosaccharides has resulted in several classes of effective LMWGs. Recently we found that certain peracetylated sugars containing anomeric triazole functional groups were effective gelators. In this study we synthesized two series of 4, 6- O -benzylidene acetal protected β-1, 2, 3-triazolyl glycoside of D-glucose and N -acetyl D-glucosamine derivatives and evaluated their self-assembling properties in a few solvents. Several gelators were obtained and the gelation properties of these compounds rely on the structures of the 4-triazolyl substituents. Typically, alkyl derivatives resulted in effective gelation in organic solvents and aqueous mixtures of ethanol and dimethyl sulfoxide. But further acetylation of these compounds resulted in loss of gelation properties. The gels were characterized using optical microscopy, rheology, and FTIR spectroscopy. We also analyzed the molecular assemblies, using 1 H NMR spectroscopy to probe the influences of the hydroxyl, amide, and triazole functional groups. Naproxen was used as a model drug and it formed co-gels with compound25 in DMSO water mixtures. Using UV spectroscopy, we found that naproxen was slowly released from the gel to aqueous solution. The general structure and gelation trend obtained here can be useful in designing sugar based biomaterials. We expect that further structural optimization can lead to more effective gelators that are compatible with different drug molecules for encapsulation and sustained release. Graphical abstract: Highlights: Molecular gelators were rationally designed from D-glucose and D-glucosamine. 4, 6- O -benzylidene acetal protected D-glucosyl triazoles were organogelators. The 3-hydroxyl group was important for molecular assembly. Naproxen formed co-gels with a gelator and slowly diffused to aqueous phase.